Implementation of the Improved Access and Quality Program according to Primary Care managers in São Paulo - e Silva, Lais Marques Coelho; Ferreira, Lucilene Renó; Rosa, Anderson da Silva; Neves, Vanessa Ribeiro (Acta paulista de enfermagem, 2017)
To analyze the implementation of the National Improved Access and Quality Program according to Primary Health Care managers. The thematic oral history was used, through semistructured interviews with five managers from Primary Health Care Services who participated actively in the two cycles of the Program in an administrative district of São Paulo City. The subjects answered the question "How do you assess the implementation process of the National Improved Access and Quality Program at this Primary Health Care Service?", among others. The analysis of the testimonies revealed the categories "The managers' perception of the implementation of the National Improved Access and Quality Program" and "Changes in the work processes since the implementation of the National Improved Access and Quality Program". The managers acknowledged the Program as a well-structured proposal, which permits a broader management view on the health services. The interviewees evidenced the use of the quality indicators, which was hardly addressed and understood in the managers and teams' daily reality though. The interviewees demonstrated that they do not understand the concepts of continuing education and institutional support. The external evaluation phase was considered subjective and without standardization, producing data that did not contribute to the assessment of the changes the teams made. The systematic incorporation process of the assessment culture to support the continuing quality improvement in Primary Health Care is incipient. Despite the continuing distance between the proposals of Primary Health Care and the practice at the Primary Health Care services studied, the Program favored the organization of the work processes and contributed to the managers' focus on the teams' practice and their own activities.